Comparison between Multiple Linear Regression Method and K-Nearest Neighbor Method for Regression on Iris Data - Adi Setiawan (Journal of Science and Science Education, 2021)
This study aims to determine the statistics used in regression models such as RMSE, MAPE, MAE and R2 using the KNN method for regression. The measure of the goodness of the method used is MAPE. The data used is iris data which has been used by many people as an example of data. Variations in the proportion of test data were carried out by 10%, 20%, 30% and 40%. In the proportion of test data of 20%, successively obtained the results that MAPE for case 1, case 2 and case 3 is 5.885 %, 7.778%, 6.979% while in case 4 is 19.341%. As a result, it is obtained that predictions using the KNN method successfully predict/forecast with highly accurate forecasting in case 1, case 2 and case 3 while in case 4 the KNN method predicts with good forecasting.